Double Telegraph Processes and Complete Market Models (2014)
The traditional jump-telegraph processes are based on a Poisson process with alternating intensities. We develop a new model based on an alternating doubly stochastic Poisson process with random intensities of jumps. Moreover, in this model the jump-telegraph process performs additional jumps each time when the intensity changes at random. Martingale measures for this type of processes are described by using Girsanov's transformation. The market model based on the doubly stochastic jump-telegraph process is studied. A class of complete models is also considered. 2014 © Taylor and Francis Group, LLC.